Silicon Grignard Reagents as Nucleophiles in Transition-Metal-Catalyzed Allylic Substitution - Xue, Weichao; Oestreich, Martin (Synthesis, 2019)
A broad range of transition-metal catalysts is shown to promote allylic substitution reactions of allylic electrophiles with silicon Grignard reagents. The procedure was further elaborated for CuI as catalyst. The regioselectively is independent of the leaving group for primary allylic precursors, favoring α over γ. The stereochemical course of this allylic transposition was probed with a cyclic system, and anti-diastereoselectivity was obtained.
Keywords: allylic substitution; copper; Grignard reagents; silicon